(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
Aim of study:the study aim to comparing the rate of cardiogenic shock and mortality rate between patient with RV infarction and inferior MI and the patient with inferior MI alone. Patient and method: Across sectional study conducted in coronary care unit in merjan medical city at time from the first of March 2014 to the 30th of September 2014 for patient with inferior MI. patients were divided to two group, the first group for patients with inferior MI and RV infarction and the second group for patients with inferior MI alone. The both groups were monitor in the hospital for any complications that can take place in the hospital stay. Result: A total of 80 patient were enrolled in the study and divided to two groups, the first group (26 patients) for patients with inferior MI and RV infarction and the second group (54 patients) for patients with inferior MI alone, both group had the same baseline characteristic. The mean age was 59.30 ± 7.56 for first group and it was 55.03 ± 5.18 for second group, male patients were 17 (65.4%) and 33 (61.1%) in the first and second group respectively. The in hospital mortality was 4 (15.4%) and 1(1.9%) in the first and second group respectively and the P value was 0.036 (significant).The risk of cardiogenic shock was 7 (26.9%) and 5 (5.6%) for first and second group respectively with P value 0.011(significant). Conclusion: 1- The patients with RV infarction and inferior MI expose to higher rate of cardiogenic shock than the patients with inferior MI alone during the time of his hospital stay. 2- The patient with RV infarction and inferior MI had higher in hospital mortality rate when compared with patient with inferior MI alone.